Constitutional History of the American Revolution - Reid, John Phillip (Book collections on Project MUSE., 1995)
Designed for use in courses, this abridged edition of the four-volume Constitutional History of the American Revolution demonstrates how significant constitutional disputes were in instigating the American Revolution. John Phillip Reid addresses the central constitutional issues that divided the American colonists from their English legislators: the authority to tax, the authority to legislate, the security of rights, the nature of law, the foundation of constitutional government in custom and contractarian theory, and the search for a constitutional settlement. Reid's distinctive analysis discusses the irreconcilable nature of this conflict--irreconcilable not because leaders in politics on both sides did not desire a solution, but because the dynamics of constitutional law impeded a solution that permitted the colonies to remain part of the dominions of George III.